Negotiating China's destiny in World War II - Van de Ven, Hans J.; Lary, Diana; MacKinnon, Stephen R. (Stanford University Press, 2015)
Before WWII, China mattered little in international relations. Afterwards, it was recognised as one of the victorious allies, it secured a permanent seat in the UN's Securty Council, and it had become a central player in East Asian Affairs. 'Negotiating China's Destiny' examines this transformation in China's international position, which occurred despite its military weakness. It examines the end of Western imperialism in China, the efforts of the Nationalists to engage with its wartime Allies, its dealings with surrounding states and peripheral areas, and its approach to Japan in defeat.